Renalase is Removed by Kidneys and During Dialysis – Excess Related to CKD Complications? - Malyszko, Jolanta; Koc-Zorawska, Ewa; Zorawski, Marcin; Kozminski, Piotr; Zbroch, Edyta; Rysz, Jacek; Banach, Maciej; S. Malyszko, Jacek (Current Vascular Pharmacology, 2015)
Background: The most common complications of chronic kidney disease (CKD) are hypertension and cardiovascular (CV) disorders. Renalase is produced and released by the kidney and also cardiomyocytes. Renalase deficiency was claimed to be responsible for hypertension and CV complication in CKD. There are contradictory data about serum renalase because of low activity and high levels revealed in hypertensive patients with CKD. We assessed serum renalase concentration in objects with CKD after one-side and both-side nephrectomy (on haemodialysis [HD]), or hemodiafiltration (HDF), in urine and ultrafiltrate in hemodialysis objects. We also evaluated the influence of hemodialysis sessions on renalase concentrations. Methods: The concentration of renalase in plasma, ultrafiltrate and urine of 100 hemodialysis patients was assessed by commercially accessible test. We evaluated renalase in 17 HDF objects and 24 healthy controls. Western Blot test was also used to assess renalase concentration. Results: Ultrafiltrate in hemodialysis objects contained renalase and there was no impact of dialysers&apos type (high-flux and low-flux). Renalase concentration of urine in control group was higher than in hemodialysis objects (n=60). The anuric group had higher renalase concentration comparing to those with remaining diuresis (p<0.001). Univariate analysis revealed the correlation between renalase concentration in plasma and in urine (r=-0.28, p<0.05) and ultrafiltrate renalase in hemodialysis group and between renalase in urine in the control group (r=0.61, p<0.01). There was a correlation between urinary renalase and residual diuresis, hemodialysis sessions non-significantly lowered renalase, the type of heparin had no effect on serum renalase levels. HDF patients had significantly lower renalase than HD patients. In Western blot analysis we found that patients after bilateral nephrectomy had the highest renalase, followed by unilateral nephrectomy. Conclusion: Kidneys eliminate renalase and it is possible that the increased renalase has the impact on cardiovascular diseases in chronic kidney disease.
Keywords: renalase